Proteção dos saberes tradicionais : a produção de um Repositório Digital Indígena no Estado de Roraima - Neves, Elton Bentes (2021)
This study proposes the construction of a technical-scientific database and cultural memory, with the aim of developing a cultural and scientific digital repository that expresses the culture of the indigenous peoples of the state of Roraima, in order to contribute to the protection of the traditional knowledge of the peoples who live in the forest, in addition to allowing their knowledge to be within the reach of global society, ensuring that culture, science and the record of social life is perennial. Of the few libraries in Roraima that have bibliographic material on this topic, none can be considered a reference, as they still have a very shy collection. Therefore, for the construction, an attempt was made to map, through scientific publications, the indigenous peoples belonging to the State, as well as to identify the Indigenous Lands within the limits of the territory; then, some informational units that hold, organize and produce traditional indigenous knowledge were highlighted; list the principles, norms and legislation about Traditional Knowledge and Intellectual Property; as for the technological process, it was necessary to present the digital libraries and their variations, which were the basis for the development of new information and communication technologies; understand the movements that gave rise to digital repositories, to maintain their principles; and finally, to present and develop a thematic digital repository, whose tool is used in other segments, in order to preserve knowledge, guarantee the protection and access to information, in an easy and free way.